2022
DOI: 10.21203/rs.3.rs-1275272/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Effects of persistent water-table level drawdown on fine-root biomass and production in different site types of a boreal forested peatland

Abstract: Purpose In peatlands, fine-root biomass (FRB) and production (FRP) and their depth distribution and plant functional type (PFT) composition are poorly known. We studied the effects of persistent water-table level drawdown on these characteristics in four forested boreal peatland site types that varied in soil nutrient and WTL regimes, ground vegetation and tree stand characteristics. Methods FRB was estimated by separating and visually identifying roots from soil cores extending down to 50-cm depth. FRP was … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Finér et al (2011) estimated that average production of fine roots for all plants (trees + understorey) in boreal and temperate forest ecosystems was 3.11 ± 2.59 t ha -1 yr -1 and 4.28 ± 3.75 t ha -1 yr -1 , respectively; however, mineral and organic (peatland) soils were not analysed separately. Lampela et al (2022) found that average fine root production in boreal forested peatland varied from 0.31 t ha -1 yr -1 to 1.20 t ha -1 yr -1 ; furthermore, there were no significant differences in total fine root production between the undrained and drained sites. Our estimates in forests with nutrient-rich organic soils showed that average fine root production ranged from 0.46 ± 0.15 t ha -1 yr -1 in deciduous-trees-dominated stands with drained organic soils to 0.69 ± 0.08 t ha -1 yr -1 in Norway spruce dominated stands with drained organic soils.…”
Section: Production Of Fine Roots and Its Affecting Factorsmentioning
confidence: 86%
See 3 more Smart Citations
“…Finér et al (2011) estimated that average production of fine roots for all plants (trees + understorey) in boreal and temperate forest ecosystems was 3.11 ± 2.59 t ha -1 yr -1 and 4.28 ± 3.75 t ha -1 yr -1 , respectively; however, mineral and organic (peatland) soils were not analysed separately. Lampela et al (2022) found that average fine root production in boreal forested peatland varied from 0.31 t ha -1 yr -1 to 1.20 t ha -1 yr -1 ; furthermore, there were no significant differences in total fine root production between the undrained and drained sites. Our estimates in forests with nutrient-rich organic soils showed that average fine root production ranged from 0.46 ± 0.15 t ha -1 yr -1 in deciduous-trees-dominated stands with drained organic soils to 0.69 ± 0.08 t ha -1 yr -1 in Norway spruce dominated stands with drained organic soils.…”
Section: Production Of Fine Roots and Its Affecting Factorsmentioning
confidence: 86%
“…In general, fine root production varies widely both within and among different types of boreal forests with organic soils (Lampela et al 2022). Yuan & Chen (2010) estimated that the average production of fine roots (< 2 mm in diameter) in boreal forest ecosystems was 2.83 t ha -1 yr -1 (both mineral and organic soils were included).…”
Section: Production Of Fine Roots and Its Affecting Factorsmentioning
confidence: 99%
See 2 more Smart Citations